Clinical, biochemical, and genetic spectrum of seven patients with NFU1 deficiency - Ahting, Uwe; Mayr, Johannes A.; Vanlander, Arnaud V.; Hardy, Steven A.; Santra, Saikat; Makowski, Christine; Alston, Charlotte L.; Zimmermann, Franz A.; Abela, Lucia; Plecko, Barbara; Rohrbach, Marianne; Spranger, Stephanie; et al. (Frontiers in Genetics, 2015)
Disorders of the mitochondrial energy metabolism are clinically and genetically heterogeneous. An increasingly recognized subgroup is caused by defective mitochondrial iron–sulfur (Fe–S) cluster biosynthesis, with defects in 13 genes being linked to human disease to date. Mutations in three of them, NFU1, BOLA3, and IBA57, affect the assembly of mitochondrial [4Fe–4S] proteins leading to an impairment of diverse mitochondrial metabolic pathways and ATP production. Patients with defects in these three genes present with lactic acidosis, hyperglycinemia, and reduced activities of respiratory chain complexes I and II, the four lipoic acid-dependent 2-oxoacid dehydrogenases and the glycine cleavage system (GCS). To date, five different NFU1 pathogenic variants have been reported in 15 patients from 12 families. We report on seven new patients from five families carrying compound heterozygous or homozygous pathogenic NFU1 mutations identified by candidate gene screening and exome sequencing. Six out of eight different disease alleles were novel and functional studies were performed to support the pathogenicity of five of them. Characteristic clinical features included fatal infantile encephalopathy and pulmonary hypertension leading to death within the first 6 months of life in six out of seven patients. Laboratory investigations revealed combined defects of pyruvate dehydrogenase complex (five out of five) and respiratory chain complexes I and II+III (four out of five) in skeletal muscle and/or cultured skin fibroblasts as well as increased lactate (five out of six) and glycine concentration (seven out of seven). Our study contributes to a better definition of the phenotypic spectrum associated with NFU1 mutations and to the diagnostic workup of future patients.